Structural insights into the redox regulation of Oncomelania hupensis TRP14 and its potential role in the snail host response to parasite invasion. Issue 128 (September 2022) - Huang, Shuaiqin; Wang, Songqing; Su, Zhiming; Cao, Yunchao; Hong, Wenbin; Lin, Tianwei
Abstract: The freshwater amphibious snail Oncomelania hupensis is the unique intermediate host of Schistosoma japonicum, but little attention has been paid to the interaction between the two. In snails, the production of reactive oxygen species (ROS) by hemocytes has been shown to be vital for snail immune defense against schistosome infection. However, excessive ROS accumulation could lead to oxidative damage, requiring the antioxidant system for maintaining the cellular redox homeostasis. Previously we identified a thioredoxin-related protein of 14 kDa from O. hupensis ( Oh TRP14), and showed that it was involved in the scavenging of ROS in circulating hemocytes. Here, we confirmed that Oh TRP14 plays a potential role in the snail host response to parasite challenge and determined the crystal structures of Oh TRP14 in two different states (oxidized and transition state). The overall structure revealed a typical Trx fold and is similar to that of human TRP14 (hTRP14), but there were significant structural differences between the two states. Noticeably, there was a different pair of thiol groups from Cys30 and Cys44 in the transition state of Oh TRP14, were with the similar separation of 2.9 Å as that (2.6 Å) between Cys41 and Cys44, but in a different orientation, suggesting that the Cys30 is likely to function as an important molecular switch involved in the oxidoreductase activity of Oh TRP14. Comparative studies between Oh TRP14 and hTRP14 by analyzing the surface characteristics, charge distribution and oxidoreductase activity toward insulin demonstrated they might have similar substrates. The results are expected to provide structural insights into the redox regulation of Oh TRP14 and contribute to better understanding of TRP14 family. Data deposition: The atomic coordinates of the structure and the structure factors were deposited in Protein Data Bank with PDB ID codes 7XQ3 and 7XPW . Highlights: Oh TRP14 plays a potential role in the redox regulation in snail host response to parasite challenge. The crystal structures of Oh TRP14 in the oxidized state and transition state were determined and characterized. Cys30 is likely to function as a molecular switch involved in the oxidoreductase activity of Oh TRP14. The protruding helix α3 and the extended loop β2-α2 could be correlated to the substrate recognition of Oh TRP14.